Why Are Youth Intent on Investing Through Peer to Peer Lending? Evidence from Indonesia - Ichwan Ichwan; Rahmatina A. Kasri (Bank Indonesia, 2019)
This study aims to analyse the factors that influence the intention of youths/millennials in Jakarta, the capital of Indonesia, to invest in Peer to Peer (P2P) lending. Due to the relative newness of P2P lending in Indonesia, the framework utilised is the Technology Acceptance Model (TAM), and the study involves around 400 youths, the majority of whom are Muslims. Further, the study employs Structural Equation Modelling (SEM) and logistic regression to analyse the influence of socio-demographic variables (gender, religion, marital status, education, employment, religion and income) on the intention to invest through P2P lending. The results of the study indicate that intention to invest in P2P lending is positively correlated and influenced by the attitude variable, which is itself influenced by factors including perceived ease of use, knowledge and trust in P2P lending. The results imply that the potential of youth to invest in P2P lending might be enhanced by improving technology (ease of use), literacy and trust in P2P lending. Moreover, it is suggested that those most interested in and more likely to invest through P2P lending are Muslims, have higher education and have higher incomes. With better literacy and marketing programmes, these groups could be targeted by P2P lending platforms to become potential investors. Lastly, the findings are expected to contribute to Islamic finance concepts and practices, particularly in the context of Indonesia.